Narrative and experience: Illness in the context of an ethnographic interview - Crivos, Marta (2002)
In the climate of methodological optimism of the 1960s and 1970s, the mere deed of going to the countryside with a tape recorder and finding an "expert" in the chosen field used to guarantee an ethnographic work academically acceptable. My encouter with oral history has to do with my frustration upon finding such tools were not sufficient to achieve the sought after "insight" into the local ideas about health and sickness in a rural community in northwest Argentina.